Study of a Biparametric Family of Iterative Methods - B. Campos; A. Cordero; Á. A. Magreñán; J. R. Torregrosa; P. Vindel (Abstract and Applied Analysis)
The dynamics of a biparametric family for solving nonlinear equations is studied on quadratic polynomials. This biparametric family includes the c-iterative methods and the well-known Chebyshev-Halley family. We find the analytical expressions for the fixed and critical points by solving 6-degree polynomials. We use the free critical points to get the parameter planes and, by observing them, we specify some values of (α, c) with clear stable and unstable behaviors.